Advanced Agrotechnologies Under Limited Water Resources: A the Battle Against Desertification in Israel - Sitton, Dov (Annals of Arid Zone, 2016)
Arid regions arc characterized by scarce unreliable precipitation together with strong solar radiation and high levels of water evaporation. Such conditions can obviously never allow the establishment of rainfed agriculture. The introduction of advanced agrotechnologies and inexpensive, yet simple to operate, drip irrigation aid in the creation of sustainable agriculture under arid conditions. The advantages of drip irrigation arc presented and discussed against a background of the experience and know-how developed in Israel.